The Effect Of Hypnotherapy On Post Traumatic Stress Disorder (PTSD) Decrease In Women Of Sexual Abuse In Tasikmalaya 2019 - Kharisma Nurul Fazrianti Rusman; Wiwin Mintarsih; Nita Nurvita (Alma Ata University Press, 2019)
Sexual abuse can have a profound trauma effect on victims, especially women. The effect of trauma experienced by victims of sexual abuse is an aotonomic liability anxiety syndrome from a very painful experience both physically and emotionally called Post Traumatic Stress Disorder or PTSD. One therapy for PTSD is hypnotherapy. Hypnotherapy is one kind of complementary /nonconventional therapy where patients are guided to relax in and naturally. The gate of someone's subconscious mind will be open, thus patients tend to be easier to accept healing suggestions given. The purpose of this study is to determine the effect of hypnotherapy on Post Traumatic Stress Disorder (PTSD) in women victims of sexual abuse 2019 in Tasikmalaya.This study used a single case experimental design within the A-B-Follow paradigm. A is a baseline measurement, and B is a measurement after administration of therapy and follow-up is the final measurement. This study involved four subjects with the criteria of women who were victims of sexual abuse in Tasikmalaya. Data analysis in this study used quantitative analysis in the form of graphical explanations of research and qualitative analysis in the form of results from observations and interviews during the study. The results of this study found that the level of PTSD women who were sexually abused before hypnotherapy was in the high and medium category. While after hypnotherapy was in the medium and low category. Hence, there is an effect of hypnotherapy on the level of PTSD women victims of sexual abuse.